A Using Sports in Integrated Drug Abuse Victim Rehabilitation Services to Support Sustainable National Rehabilitation - Arifin Ika Nugroho; Amin Pujiati (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. Indonesia is currently dealing with a significant issue. The situation is complex and worrying, as the youth attending school are the most affected by substance abuse. Students who struggle with substance abuse are often immediately ostracized by society. The focus of the services provided does not prioritize the recovery from addiction, as there is more emphasis on healing with limited space for personal development. Well-implemented, measurable, progressive, and structured sports activities have a positive impact on the health and overall quality of life of athletes. There are substantial growth opportunities in the sports industry, particularly in the industrial sector. The sports sector can tap into different market segments through the three categories mentioned above. Materials and Methods. The research is a qualitative descriptive investigation that utilized observation, interviews, and documentation to gather data. The study focused on individuals working as tourist attraction managers, sports event organizers, and sports industry practitioners. Data validity was ensured by collecting and cross-referencing information from reliable sources. The SWOT analysis approach was used to analyze the data, which involved data reduction, presentation, and conclusion. This analysis was conducted about the development of rehabilitation service centers in Indonesia. Results. Indonesia is facing a rise in drug abuse victims needing rehabilitation. This requires enhancing institutions, establishing effective regulations, and creating integrated service standards. Collaboration between the sports industry and other sectors is needed to maximize tourism potential. The focus is on developing Integrated Drug Abuse Victim Rehabilitation Services using Sports Exercise Therapeutic Management for both preventive and curative treatment. Conclusion. Rehabilitation programs that integrate sports and exercise as part of the treatment for individuals struggling with drug abuse are essential for their recovery. Therapeutic management plays a critical role in implementing these interventions. The development and enhancement of sports services can significantly improve the effectiveness of these interventions, ultimately leading to a reduction in the prevalence of drug addiction among individuals who have not been previously affected.